2019
DOI: 10.1039/c8ta11735g
|View full text |Cite
|
Sign up to set email alerts
|

A high-voltage aqueous lithium ion capacitor with high energy density from an alkaline–neutral electrolyte

Abstract: A proof-of-concept lithium ion capacitor comprising LiMn2O4 nanorods as the cathode, a nitrogen-rich biomass carbon anode and a stable alkaline–neutral electrolyte was designed and fabricated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 69 publications
2
33
0
Order By: Relevance
“…[ 42–44 ] Additionally, the performance of the energy density of TCCS NiCo 2 S 4 //Fe 1−x S/rGOA AHC outperformed that of other state‐of‐the‐art structures that combine nickel–cobalt or manganese oxide/sulfide‐based cathode and EDLC‐type carbon‐based anode electrodes [ 25,45–47 ] and led to higher energy density than those of previous aqueous lithium‐ion capacitors (Table S3, Supporting Information). [ 48–49 ] Additionally, the cycling performance of TCCS NiCo 2 S 4 //Fe 1−x S/rGOA AHC at a high‐current density of 10 A g −1 (Figure 6h) showed that 90.2% of the initial capacitance was maintained after 50 000 cycles. Furthermore, the columbic efficiency remained high (≈100%) for over 50 000 cycles.…”
Section: Resultsmentioning
confidence: 99%
“…[ 42–44 ] Additionally, the performance of the energy density of TCCS NiCo 2 S 4 //Fe 1−x S/rGOA AHC outperformed that of other state‐of‐the‐art structures that combine nickel–cobalt or manganese oxide/sulfide‐based cathode and EDLC‐type carbon‐based anode electrodes [ 25,45–47 ] and led to higher energy density than those of previous aqueous lithium‐ion capacitors (Table S3, Supporting Information). [ 48–49 ] Additionally, the cycling performance of TCCS NiCo 2 S 4 //Fe 1−x S/rGOA AHC at a high‐current density of 10 A g −1 (Figure 6h) showed that 90.2% of the initial capacitance was maintained after 50 000 cycles. Furthermore, the columbic efficiency remained high (≈100%) for over 50 000 cycles.…”
Section: Resultsmentioning
confidence: 99%
“…K + ‐Conducting Membrane was prepared according to our recent works . Waste Nafion NR117 membrane (purchased from Yinfeng New Energy Co. Ltd.) was used as raw material and treated with the following three steps to prepare the K + ‐conducting membrane (DKJ‐01).…”
Section: Methodsmentioning
confidence: 99%
“…The preparation process of Li + -conducting membrane was similar to the recent works. [60,61] Waste Nafion NR117 membrane (purchased from Yinfeng New Energy Co. Ltd.) was used as raw material and treated with the following three steps to prepare the Li + -conducting membrane. At first, wasted Nafion 117 membrane was treated with 3 wt% H 2 O 2 aqueous solution and stirred for 1 h at 80 °C in water bath.…”
Section: Materials and Methods-preparation Of LI + -Conducting Membranementioning
confidence: 99%